Thyrotoxicosis with pegylated interferon alfa-2b. - Lowndes, SA; Asher, R; Middleton, MR (2010)
BACKGROUND: Despite adequate surgery, a diagnosis of stage III melanoma carries a high risk of relapse, and hence mortality. Interferon alfa is the only treatment that has currently been shown to alter the natural history of the disease, delaying relapse-free survival, particularly in patients with micrometastatic disease. There is also recent evidence of a prognostic advantage conferred by the development of autoimmune conditions in patients receiving adjuvant interferon therapy. OBSERVATIONS: We present the case of a 27-year-old woman with stage IIIa melanoma who was entered into the European Organisation for the Research and Treatment of Cancer 18991 trial of 5-year adjuvant treatment with pegylated interferon (peginterferon) alfa-2b. The patient developed thyrotoxicosis 3 months after commencing treatment, which required treatment with propylthiouracil. The degree of thyrotoxicosis corresponded closely to the dose of peginterferon alfa-2b given. However, in this patient, the hyperthyroidism resolved spontaneously after 4 years when peginterferon treatment was still ongoing. Seven years following the initial diagnosis, the patient has not had disease relapse. CONCLUSION: Hyperthyroidism is less common than hypothyroidism as a consequence of interferon therapy, and this case is atypical in that it resolved spontaneously during interferon therapy but is in accordance with the recent evidence of a positive association between interferon-associated autoimmunity and prognosis.